Elementary Schools of Art in Hungary are the Key to Increasing One’s Chances, Disadvantage Compensation and Multilateral Self-Development - Kiss, Julianna (Central European Journal of Educational Research, 2021)
Bibliography of the reviewed book: Szűcs, T. (2019). Az alapfokú művészeti iskola, egy esélynövelő iskolatípus. Debrecen: Debreceni Egyetemi Kiadó. 190., 978-963-318-768-5.